PENERAPAN ETIKA BISNIS ISLAM TERHADAP JUAL BELI PAKAIAN BEKAS IMPOR DITOKO SANDANG MURAH BOJONEGORO - Muklisshotun; H.Noho, Muhammad Dzikirullah (Irtifaq, 2021)
Clothing is a community need that is used for their daily activities. Fashion and lifestyle that are increasingly developing encourage people to show their identity, this has led to rampant sales of imported used clothing and increasingly high business competition. For this reason, business ethics in accordance with Islam and syari'ah rules are very important to be considered in carrying out business activities in this case buying and selling. This type of research is a type of empirical juridical research and uses the socio-legal research method. The data source, primary data, comes from primary data (sourced from direct questions and answers in the field), secondary (reading books or documents) and tertiary (dictionaries). The location that is the place of research is at the Bojonegoro Cheap Clothing store in Bojonegoro Regency. The results of this study indicate that the trading practices carried out by traders or business actors in terms of Islamic business related to buying and selling have been fulfilled, while the buying and selling requirements have not been fulfilled. And if there is one of the pillars or the conditions in the sale and purchase are not met, the sale and purchase is canceled. Meanwhile, the application of Islamic business ethics has been well implemented by traders such as the principles of justice, free will, and honesty, while the principles of responsibility and devotion have not been applied by the seller. Therefore, buying and selling must be really paid attention to so that the sale and purchase is valid and in accordance with the Islamic laws and regulations. Keyword: Used imported clothes, Buy and sell, Islamic business ethics